Sumatran tiger identification and phylogenetic analysis based on the CO1 gene: Molecular forensic application - ASHRIFURRAHMAN ASHRIFURRAHMAN; SARUEDI SIMAMORA; RUSDIYAN RITONGA; WILSON NOVARINO; DJONG HON TJONG; RIZALDI RIZALDI; SYAIFULLAH SYAIFULLAH; DEWI IMELDA ROESMA (Society for Indonesian Biodiversity, 2022)
Abstract. Ashrifurrahman, Simamora S, Ritonga R, Novarino W, Tjong DH, Rizaldi, Syaifullah, Roesma DI. 2022. Sumatran tiger identification and phylogenetic analysis based on the CO1 gene: molecular forensic application. Biodiversitas 23: 1788-1794. Wild animal hunting, especially in the Sumatran tiger (Panthera tigris sumatrae), has been caused the population decline. Regulation and law enforcement have been implemented even though it does not affect optimal because of the trickery of poachers and illegal traders. Sometimes, the evidence of P. t. sumatrae derivative products, for example, bones, nails, skins, hair, and other body parts, cannot be properly identified to raise the cases. However, genetic markers, such as the CO1 gene, have successfully identified illegal trafficking samples. This study used 20 samples, consisting of seven samples (four preserved hairs, two claws, one bone) that were suspected of P. t. sumatrae collected from illegal wildlife trade cases in West Sumatra, Indonesia. Other thirteen samples were twelve blood and one hair of P. t. sumatrae samples were collected from the Dharmasraya Sumatran Tiger Rehabilitation Center (PR-HSD). All samples were isolated, Polymerase Chain Reaction (PCR), sequenced, and 999 base pairs (bp) of the CO1 gene sequences were analyzed. In addition, National Center for Biotechnology Information (NCBI) data sequences including two P. t. sumatrae sequences, four P. t. altaica sequences, one P. t. amoyensis sequence, one P. t. corbetti sequence, three P. pardus sequences, and one Felis catus sequence were collected for comparison and supporting data. The result confirmed that all samples in this study were P. t. sumatrae. We determined those depending on similarity value which was 99.60%-99.70% with P. tigris reference sequence (NC_010642.1) and 99.90%-100% with P. t. sumatrae (JF357969.1). Phylogenetic analysis supported species identification with average intraspecies sequence divergence was 0 to 0.4% and presented the monophyletic group. This study was the first and most recent report to use seized samples to identify P. t. sumatrae based on the CO1 gene in West Sumatra, Indonesia.